تطبيقات تكنولوجيا الإعلام والاتصال والخرس الأسري: تطبيق الفايسبوك أنموذجا - بلحضري، بلوفة Belhadari, Bloufah (جامعة الجزائر1 بن يوسف بن خدة, 2022)
تقودنا بعض الدراسات النظرية والإمبريقية المقامة حول علاقة التطبيقات الحديثة لوسائل تكنولوجيا الإعلام والاتصال بالتغير الاجتماعي، نحو خلاصة مفادها أن تزايد حجم استخدام الأفراد لوعاء الفيسبوك؛ قد أدى بهم إلى الانغماس في نقلة اتصالية مفتوحة الآفاق إلى درجة تزايد معها حجم التوجس من ظهور محددات جديدة للتواصل فيما بينهم بما يبعث على تهديد كيان تواصلهم الفيزيقي. بالمقابل؛ تستوقفنا دراسات أخرى وهي من هذه الرؤية على وجه النقيض، والتي تتجه إلى التخفيف من حدة وطأة هذا التوجس الذي يبدو أنه مبالغ في شأنه. وإذا كانت هذه الإشكالية تتخذ أبعادًا كثيرة من حيث تعدد وجهات النظر التي يمكن أن تصادفنا في خضم تشريح تلافيف سؤال مدى التأثير؛ فإنه ثمة إجابة ستقودنا حتمًا للاعتراف بإلزامية عرض مساءلة تتكشف من خلالها مدى إمكانية ترجيح الكفة إلى أحد الحكمين للوقوف على حقيقة الأثر الذي يمكن أن يخلفه استخدام تطبيق "الفيسبوك" على مساحة الاتصال داخل الأسرة الجزائرية واتجاهه بها نحو خرس أسري من دون ذلك. Some theoretical and empirical studies conducted on the relationship of modern applications of communication technology to social change lead us. Towards a conclusion that the increasing volume of individuals' use of the Facebook bowl led them to indulge in a communication shift with open horizons that raises apprehension about the emergence of new determinants of communication between them, to a degree that could threaten the entity of their physical communication. On the other hand; Other studies stop us from this view on the contrary, which tends to alleviate this apprehension that seems to be exaggerated. If this problem takes many dimensions in terms of the multiplicity of viewpoints that we may encounter in the midst of dissecting convolutions of the question of the extent of influence; There is an answer that will inevitably lead us to acknowledge the obligation to present accountability through which reveals the extent to which it is possible to tip the scale to one of the two judgments to find out the reality of the impact of the use of the "Facebook" application on the communication space within the Algerian family and its direction towards family silence without that.
Keywords: العزلة الاجتماعية -- العلاقات الأسرية -- تطبيقات التواصل الاجتماعي -- الأسرة الجزائرية